CONCEPTION OF A DIGITAL TWIN IN MECHANICAL ENGINEERING – A CASE STUDY IN TECHNICAL PRODUCT DEVELOPMENT. (May 2020) - Schweigert-Recksiek, S.; Trauer, J.; Engel, C.; Spreitzer, K.; Zimmermann, M.
Abstract: A Digital Twin as a virtual representation of a physical system is becoming a key technology. While potential benefits are evident, there is no approach in literature or practice comprehensively supporting its introduction. In an industrial case study, a generic procedure model for the conception and implementation of a Digital Twin was developed. The relations between use cases, usage data, and virtual models resulted in a target concept as well as requirements for the implementation. Thereby, companies can access the potentials of a Digital Twin taking into account their specific situation.